1999
DOI: 10.1159/000015355
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization and chromosome location of the mouse Elongin A gene (<i>Tceb3</i>)

Abstract: Elongin A is the transcriptionally active subunit of the Elongin complex, which strongly increases the rate of elongation by RNA polymerase II by suppressing the transient pausing of the polymerase at many sites within transcription units. In the present study, we obtained the cDNA sequence of the mouse Elongin A gene (Tceb3) and characterized its genomic structure. The deduced 773-amino acid sequence of mouse Elongin A shows 91% and 81% identity with rat and human Elongin A, respectively. The Elongin A gene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…As shown in Fig. 2, the Elongin A3 probe hybridized to a single band of ϳ5.0 kb and, consistent with previous studies, the Elongin A-specific probe hybridized to two mRNA species of ϳ5.2 and ϳ2.8 kb (10,28). To correct for the amount of RNA loaded in each lane, we measured the intensity of each of the bands on the blot after the hybridization with the ␤-actin probe.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in Fig. 2, the Elongin A3 probe hybridized to a single band of ϳ5.0 kb and, consistent with previous studies, the Elongin A-specific probe hybridized to two mRNA species of ϳ5.2 and ϳ2.8 kb (10,28). To correct for the amount of RNA loaded in each lane, we measured the intensity of each of the bands on the blot after the hybridization with the ␤-actin probe.…”
Section: Resultssupporting
confidence: 83%
“…What is the mechanism by which Elongin A is activated by (10,28,(31)(32)(33). It has also been reported that Elongin A is predominantly localized in the nucleus (25,34).…”
Section: Fig 3 Elongin A3 Forms a Complex With Elongins B And C Amentioning
confidence: 97%
“…We first isolated and analyzed the structure of the mouse Elongin A gene (19). A gene-targeting vector was then constructed by replacing exons 8 -10 of the Elongin A gene, which encode the domain essential for its transcriptional elongation activity (15), with a pol II-neo-poly(A) cassette (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clones-A 15-kb genomic fragment spanning the sequence encoding exons 2-11 and the 3Ј-UTR of murine Elongin A was isolated from a 129/Sv mouse genomic library, using a mouse Elongin A cDNA probe (19). Genomic fragments of 4.5 and 1.4 kb flanking exons 8 -10 of Elongin A were used to generate a targeting construct in which exons 8 -10 were replaced by a pol II-neo-poly(A) cassette (20).…”
Section: Generation Of the Elongin A-deficient Es Cellmentioning
confidence: 99%
“…19 To examine whether Elongin A is expressed when such lethality occurs, we analyzed its expression at different developmental stages in wild-type (WT) embryos. A high level of Elongin A mRNA was detected in E4.5 embryos and was thereafter sustained throughout embryogenesis (Figure 1d), suggesting that Elongin A plays a critical role in embryonic development.…”
Section: Resultsmentioning
confidence: 99%